A Causal Study of Role Play Technique and Drilling Vocabulary to the Students’ Speaking Ability - Ayu Oktaviani; Nurbianta Nurbianta (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
In this era of Globalization, English Language is important for our lives. In fact, it is the second most spoken language in the world. Globalization made the use of English language more widen. The ability to speak and to write English property has been one essential benchmark skills in the professional world. The teacher can use some methods in teaching and learning process to help the students’ understanding. In this research, the researcher used role play technique and drilling vocabulary to enhance speaking skill. This research problems were; (1) Is there any influence of role play technique to the students’ speaking ability at SMA MUHAMMADIYAH TANJUNG REDEB?, (2) Is there any influence of drilling vocabulary to students’ speaking ability at SMA MUHAMMADIYAH TANJUNG REDEB?, (3) Is there any influence of role play technique and drilling vocabulary to the students’ speaking ability at SMA MUHMAMMADIYAH TANJUNG REDEB?. The method of this research is partial correlation method, The statistic value performed in level good correlation among Role play technique and drilling vocabulary to the students’ speaking ability during conducted for twelve at SMA Muhammadiyah Tanjung Redeb.